Dodaj sumy i wykonaj redukcję wyrazów podobnych:
a) (-2x+3y) + (5x - 5y+1) =
b) (7a +9b)+(-4x - 5b-4) =
c) (-0,5x- 0,2y)+(x+0,7y+1) =

Wykonaj odejmowanie sum algebraicznych i zredukuj wyrazy podobne:
a) 6a -(-2a-5) =
b) (8x-1)-(5x-4)=
c) (10x² +6)-(-4x² + 2x -1)=
d) (4x+2y-1)-(-3x-4y+3)=



1

Odpowiedzi

2010-01-13T20:36:06+01:00
A) (-2x+3y) + (5x - 5y+1) =-2+3y+5x-5y+1=5x-1-2y
b) (7a +9b)+(-4x - 5b-4) =7a+9b-4x-5b-4=7a+4b-4x-4
c) (-0,5x- 0,2y)+(x+0,7y+1) = -0,5x-0,2y+x+0,7y+1=0,5x+0,5y+1

a) 6a -(-2a-5) =6a+2a-5=8a-5
b) (8x-1)-(5x-4)=8x-1-5x+4=3x+3
c) (10x² +6)-(-4x² + 2x -1)=10x²+6+4x²-2x+1=14x²+7-2x
d) (4x+2y-1)-(-3x-4y+3)=4x+2y-1+3x+4y-3=7x+6y-4